Spin-offs and Operating Performance - CATON, Gary L. (Institutional Knowledge at Singapore Management University, 2012)
This study examines the relation between changes in industry-adjusted operating performance associated with corporate spin-offs and the market’s assessment of the spin-off as either a value increasing or value decreasing activity. I find that the average change in industry-adjusted operating performance associated with my sample of spin-offs is not significantly different from zero. However, I also present evidence suggesting that this average result is misleading because some spin-offs appear to be value increasing while others are value decreasing. I establish that a positive and significant relation exists between parent company revaluation and a) the change in industry-adjusted operating performance of the combined but independent units, and, b) whether the parent and spun-off unit operated in different lines of business. Tests for the sensitivity of the results to underlying assumptions show that these results are robust. I conclude that some spin-offs create value, especially those in which the parent and the unit spun-off are in unrelated lines of business. However, I also conclude that some spin-offs destroy value.